2021
DOI: 10.7150/ijms.48281
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of initial chest CT findings for clinical outcomes in patients with COVID-19

Abstract: Rationale: To identify whether the initial chest computed tomography (CT) findings of patients with coronavirus disease 2019 (COVID-19) are helpful for predicting the clinical outcome. Methods: A total of 224 patients with laboratory-confirmed COVID-19 who underwent chest CT examination within the first day of admission were enrolled. CT findings, including the pattern and distribution of opacities, the number of lung lobes involved and the chest CT scores of lung involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Identifying admission CT predictors of adverse outcome in patients without underlying medical issues would help to identify the most vulnerable patients in this age range and, as a result, change their therapy. Several recent studies reported imaging CT findings of patients with adverse outcomes (12)(13)(14)(15). However, data on the outcomes of consecutive patients, factors influencing hospital admission vs. outpatient management, and risk factors for COVID-19 adverse effects is still lacking in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying admission CT predictors of adverse outcome in patients without underlying medical issues would help to identify the most vulnerable patients in this age range and, as a result, change their therapy. Several recent studies reported imaging CT findings of patients with adverse outcomes (12)(13)(14)(15). However, data on the outcomes of consecutive patients, factors influencing hospital admission vs. outpatient management, and risk factors for COVID-19 adverse effects is still lacking in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Liu et al [ 8 ], which used the same criteria as the present study used for the disease severity (WHO), number of lung lobes involved and total CT score were directly correlated to disease severity. In other study, it was stated that the odds of adverse outcome (need for mechanical ventilation or mortality) is four times higher in patients with more than four lung zones involved than in those without [ 15 ]. Auger et al [ 16 ] reported that ground glass, crazy paving, and consolidation did not have a significant association either with invasive endotracheal ventilation or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…More studies showed the CT score calculated by their scoring systems was significantly higher in critical and severe than in mild and common category [ 18 , 19 , 22 ]. Other studies found that the overall lung involvement score had predictive value for clinical severity and ICU admission, and higher chest CT score was significantly associated with an increase in requirement of oxygen and even mechanical ventilation [ 16 , 25 27 , 36 , 37 ]. CT involvement score can help early diagnosis, severity assessment and treatment of COVID-19 [ 9 , 38 , 39 ] and may indicate the progression and recovery of the disease [ 6 , 40 ].…”
Section: Discussionmentioning
confidence: 99%